Bedouin Culture in the Poetry of Abu Shraa AlQaisi (Deid in 280 AD) (Journal of Hama University, 2025)
This study tries to explore the elements of Bedouin culture that Abu Shraa used to form his poetic meanings as seen in his poetry which survived to reach modern readers. Most of his poetic meanings was prevailing among ancient Arab poets with some variations in the style of poetic structures.Although Abu Shraa could add his own emotions and distinctive creative vision to his poetic meanings, most of his poetry was clearly influenced by Bedouin culture. It is evident that Bedouin culture which sprang from Arabian Peninsula (Jazeera) at the hands of Jahelia poets and post Jahelia ones had a distinct influence on Abu Shraa’s use of its elements although he is not Bedouin. He lived in Busra in a flourishing environment where Arabic culture was open to other cultures and the poetic contexts were influenced by cultural, social and intellectual changes that affected Abbasi society.Accordingly, it is important to acknowledge Abu Shraa’s personality and to study the key terms relevant to Bedouin culture both lexically and contextually.Thus, this study explores the poetic connotations of traditional Bedouin Arab culture that affected Abu Shraa since many behavioral and social values related to this culture appeared in his poetry such as: generousity, pride in family and tribe, ethics of loyalty, faithfulness, commitment, bravery, manness, and love towards relatives even if they were cruel. Moreover, woman’s presence in Abu Shraa’s poetry and his style of emplying her status go in accordance with Bedouin culture.The study has been inspired by a deep reading of the available Abu Shraa's poetry that has been gathered in more than one attempt. The study has used the descriptive analytical approach to get its results:-The poet started from his original traditional Bedouin culture rooted in himself to prove his distinguished poetic ability.-Having the essence of poetic meanings linguistically and semantically, he added his own capacities and his loving soul towards his origin and rich Arabic culture.-He was a significant poet even if he lacked the deserved poetic canon die to the loss of his poetry.-He was very little influenced by innovative poetry in comparison to his great preference of originality school, its culture and affecting elements.